Meningkatkan Penulisan Konten Instagram untuk Promosi Pariwisata di Sulawesi Barat - Kurnia, Kurnia; Pratiwi Samad; Abdul Wahab (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
The background of this study is based on the need to strengthen English language skills and digital marketing capabilities among members of GenPI Sulbar in the West Sulawesi province. In today's digital era, social media, particularly Instagram, plays a crucial role in tourism promotion. Therefore, enhancing skills in crafting engaging and informative content on Instagram is considered essential for attracting the attention of both domestic and international tourists. In this context, the members of GenPI managing the @genpi_sulbar account require improved English language and digital content creation skills to enhance the appeal of local tourist destinations. The purpose of this research is to enhance the English language abilities of Instagram account managers in Western Sulawesi who are associated with the @genpi_sulbar account. In this study, qualitative research techniques are used, and the tools used include in-depth interviews and the findings obtained from analyzing papers. Participants in the Genpi program participated in activities such as the formulation of ideas, planning, editing, and the use of tools such as Deepl, Quillbot, and Grammarly in order to assist them in improving their English language abilities. According to the findings, there was an increase in the level of comprehension of tourist marketing participants, as well as an improvement in originality, vocabulary, and the ability to effectively write content for Instagram. As a result of this study, members of GenPi were able to enhance their Instagram post writing on social media in order to promote tourism in a direct and strategic manner while simultaneously enhancing citizen awareness on a global and local scale.